Emergency : stories - Alcott, Kathleen (W. W. Norton & Company, 2023)
"The author of three critically acclaimed novels including Infinite Home returns with collection of prizewinning stories starring women confronting the hidden perils of class ascension and the emotional debts still owed from their past lives. A professor finds a photograph of her deceased mother in a compromising position on the wall of a museum. A twenty-something's lucrative remote work sparks paranoia and bigotry. A transplant to a new city must make a choice about who she trusts when her partner reveals a violent history. The summer after her divorce from an older man, an exiled painter's former friends grapple with rumors that she attempted to pass as a teenager." --